Survivors of the Flood. The Book of the Wrecked by Sydor Rey as a Holocaust Robinsonade - Janik, Gaweł (Porównania, 2019)
The article is an attempt to read the set of stories The Book of Wrecked (1959) by the Polish-Jewish writer Sydor Rey as a specific type of Holocaust Robinsonade. The author indicates how the text deals with the subject of the Holocaust by transforming Defoe’s traditional model. He draws attention to the metonymisation of the Holocaust used in the volume, which is presented as a disaster, cataclysm or defeat, and is compared to the Old Testament flood. The researcher reads the The Book of Wrecked as an implementation of anti-utopian Robinsonade in which the classic myth of the survivor’s metamorphosis is not realized. As a result, the characters of the stories constantly balance on the border between life and death.